The Impact of Corporate Social Responsibility on the Financial Stability of Banks: An Analytical Study of a Sample of Banks Listed on the Iraq Stock Exchange - Mays Kariem Jabbar; Bilal Noori Saeed (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Given the important objectives that banks strive to achieve through financial stability and their role in ensuring its continuity and ability to face various economic challenges, many have expanded their policies beyond their traditional functions by adopting a range of additional practices and activities that contribute to strengthening their developmental role in society. Among the most prominent of these practices are corporate social responsibility (CSR) activities, which have become a crucial aspect of the work of contemporary financial institutions. In this context, this research highlights CSR practices in banks. It relied on a sample of nine Iraqi banks listed on the Iraq Stock Exchange, which are characterized by their continued banking operations and regular publication of their annual financial reports. The research period was set from 2014 to 2023, and included a set of statistical tests that incorporated a number of financial determinants as control variables to determine their contribution to enhancing the impact of CSR when included alongside it, and to define the nature of the relationship between the research variables. We have reached a number of conclusions, most notably that when regulatory variables are included in the analysis model, this effect becomes statistically insignificant, which indicates that banks’ interest in internal financial factors still outweighs their interest in social aspects.